ANALISIS PERENCANAAN SUMBER DAYA MANUSIA PADA PERUSAHAAN DAERAH AIR BERSIH DAERAH ISTIMEWA YOGYAKARTA - Dedi Risdiyanto; Muhammad Mathori (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
This study aims to analyze the planning of Human Resources (HR) and the organizational structure in the Regional Water Supply Company of the Special Region of Yogyakarta so that it can immediately operate. The focus of research is HR planning, HR fulfillment and the ideal Organizational Structure. This type of research is qualitative, descriptive. Data were collected by means of literature study, in-depth interviews and documentation. Analytical methods are interpretation, editing, analysis and transcripts of recording devices, described in appropriate language and easily understood by researchers, stakeholders and report users. The research report concludes with a more essential understanding and with an invariant structure, gaining clarity for implementation. The results of the analysis are in accordance with the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia Number 52 of 2014 concerning Guidelines for the Preparation of Micro Manpower Planning in Companies, BUMN and BUMD which will be determined by governor regulation. Organizational structure and HR planning that are simple in Perumda. Clean Water is the Managing Director, General Director, Technical Director, General and Personnel Section, HR Subdivision, Information Technology and Equipment Subdivision, Finance Section, Cash Subdivision, Budget and Asset Management, Accounting Sub Division, Engineering Sub Division, Production Sub Division , Subdivision of Distribution and Services, Subdivision of Mechanical and Electrical, Business Development Section, Subdivision of Marketing and Network Development and Sub-Division of Customer Relations. The recruitment method for fulfilling HR for Directors is the prerogative right of the Governor together with the Supervisory Agency while for HR positions the Divisions use the Computer Assisted Test (CAT) mechanism.